Reconstructing a perspective of time: a micro distillery mediating the balance between tradition and modernity in an effort to revive the whispers of Graaff-Reinet’s grapes - Van der Merwe, Es-Mari (University of the Free State, 2023)
Nestled within the vast expanse of the Karoo plain, Graaff-Reinet emerges as a fertile oasis, containing a rich historical context, and unveiling a captivating tapestry of stories and narratives etched into the urban fabric. Within this narrative lies a forgotten fragment of time, known as the Withond brandy. It stands as a relic from the era of Graaff-Reinet’s vineyards, a tangible link to the past. The unveiling of the forgotten narrative provides an opportunity to extend the narrative of Graaff-Reinet’s traditions, whilst introducing a new sense of modernity into the town’s enduring 19th-century framework. Considering exploration between traditional and present architecture poses the question: How can the re-engagement of the forgotten narrative of Withond capture the essence of Graaff-Reinet’s traditionality whilst contributing to contemporary and functional development? This project attempts to enter the epoch of the vineyards by reconstructing and tracing the origins and history of the Withond brandy. It aims to seamlessly extend the current narrative by mediating Graaff-Reinet’s traditionality while embracing modernity, and by interpreting the essence of the Cape Dutch vernacular architecture rather than imposing itself on the context. The micro-distillery, a tribute to Withond’s legacy, aims to weave together the polarities that exist within Graaff-Reinet - connecting the threads of its contextual attributes, historical narrative, functional experiences, and a contemporary touch of its architecture.
Dissertation(M.Arch.(Architecture))--University of the Free State, 2023
Keywords: Unveiling of narratives; Urban narratives; Withond brandy; Cape Dutch vernacular architecture; Interpretation of architecture; Epochs; Graaff-Reinet, South Africa; Connecting polarities; Vineyards, South Africa; Modernity